Euripides’ Quotes in Pseudo Iustinus’ treatise De monarchia (Minerva, 2024)
Among the works attributed to St Justin, the late second century Christian writer, there is a brief treatise titled De Monarchia. The attribution, not the authorship, is loosely based on questions of style and content based on the testimony of Eusebius of Caesarea (HE IV 18.4). This brief treatise, with a clear Judeo-Hellenistic origin, is almost entirely comprised of an accumulation of quotes from Greek poets woven together by the common thread of their criticism of traditional religiosity that emphasizes the recognition of a single and just God. In this article we propose an analysis of Euripides’ quotes that can lead us to the conclusion of the use of previous anthologies by its author.
Keywords: Pseudo Iustinus; anthology; Euripides; quotation; judeo-hellenismus